Pengaruh Struktur Modal, Leverage, Pertumbuhan Penjualan dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Sektor Property dan Real Estate di BEI Tahun 2023-2024 - Fira Aisyah Meilani; Yulita Triadiarti (Pusat Riset dan Inovasi Nasional, 2026)
Financial conditions within the property and real estate sector have experienced significant fluctuations recently. These changes are believed to be closely linked to macroeconomic instability and the dynamics of funding policies implemented by individual firms. This study aims to empirically examine the impact of capital structure, leverage, sales growth rate, and firm size on financial performance. The scope of the study covers property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. Sample selection was conducted using a purposive sampling method, resulting in 74 out of 92 companies that met the established criteria throughout the research period. Data analysis was performed using SPSS software by applying a multiple linear regression model. Hypothesis testing was carried out through the t-test to measure the individual influence of independent variables on the dependent variable, as well as the F-test to measure the simultaneous effect. The findings of this research indicate that capital structure, leverage, sales growth, and firm size each exert a significant influence on financial performance